A novel allele of the P‑starvation tolerance gene OsPSTOL1 from African rice (Oryza glaberrima Steud) and its distribution in the genus Oryza - Pariasca-Tanaka, J.; Chin, J.H.; Dramé, K.N.; Dalid, C.; Heuer, S.; Wissuwa, M. (Springer, 2014)
We have developed allele-specific markers for molecular breeding to transfer the PSTOL1 gene from Kasalath to African mega-varieties, including NERICAs, to improve their tolerance to P-deficient soil. The deficiency of phosphorus (P) in soil is a major problem in Sub-Saharan Africa due to general nutrient depletion and the presence of P-fixing soils. Developing rice cultivars with enhanced P efficiency would, therefore, represent a sustainable strategy to improve the livelihood of resource-poor farmers. Recently the Pup1 locus, a major QTL for tolerance to P deficiency in soil, was successfully narrowed-down to a major gene, the protein kinase OsPSTOL1 (P-starvation tolerance), which was found to be generally absent from modern irrigated rice varieties. Our target is to improve the tolerance of African mega-varieties to P deficiency through marker-assisted introgression of PSTOL1. As a first step, we have determined the Pup1 haplotype and surveyed the presence or absence of PSTOL1 and other genes of the Pup1 locus in African mega-varieties, NERICAs (New Rice for Africa) and their Oryza glaberrima parents. Here, we report the presence of a novel PSTOL1 allele in upland NERICAs that was inherited from the O. glaberrima parent CG14. This allele showed a 35 base-pair substitution when aligned to the Kasalath allele, but maintained a fully conserved kinase domain, and is present in most O. glaberrima accessions evaluated. In-silico and marker analysis indicated that many other genes of the Kasalath Pup1 locus were missing in the O. glaberrima genome, including the dirigent-like gene OsPupK20-2, which was shown to be downstream of PSTOL1. We have developed several allele-specific markers for the use for molecular breeding to transfer the PSTOL1 gene from Kasalath to African mega-varieties, including NERICAs.